Treatment Patterns and Clinical Outcomes for Central Retinal Vein Occlusion in the Antivascular Endothelial Growth Factor Era. (January 2020) - Stallworth, Jeannette Y.; Thomas, Akshay S.; Constantine, Ryan; Stinnett, Sandra S.; Fekrat, Sharon
Purpose: This article describes treatment patterns and visual outcomes for central retinal vein occlusion (CRVO) in the antivascular endothelial growth factor (anti-VEGF) era. Methods: A retrospective cohort study of eyes diagnosed with CRVO between 2009 and 2016 was conducted. Treatment history and visual acuity (VA) measurements were abstracted from medical records and analyzed. Results: A total of 476 eyes of 476 patients (median age 67 years, median follow-up 25.4 months) were included. Optical coherence tomography was obtained in 93.9% and fluorescein angiography in 80% of cases on presentation. Mean VA at presentation and final visit was 20/60 and 20/94, respectively, for eyes with nonischemic CRVO, whereas that of ischemic cases remained worse than 20/800 at final follow-up. Intravitreal bevacizumab was the most common first treatment (42.2%). Intravitreal steroid was the first treatment in 3.6% and ultimately administered in 11.3% of eyes. In the first year, an average of 5.2 ± 3.6 and 2.2 ± 3.4 anti-VEGF injections were given in treatment-naive and nontreatment-naive eyes, respectively. Conclusions: In our real-world cohort, anti-VEGF injection burden and frequency are lower than in published clinical trials. Visual outcomes in both ischemic and nonischemic eyes with CRVO are poorer than expected and worse than those recorded in controlled trial settings.